Pengaruh Motif Penggunaan Fitur Close Friends Instagram Terhadap Pengungkapan Informasi - Simanungkalit, Sylvi Alexandra; Barus, Rehia Karenina Isabella (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study aims to analyze the influence of motives for using the Instagram Close Friends feature on the delivery of personal information among psychology students of Medan Area University, class of 2021-2022. The Close Friends feature allows users to share stories with a limited audience, which increases control over privacy and facilitates self-disclosure. In order to approach this problem, references such as indicators of motives for using the Instagram Close Friends feature and disseminating information are used. This study uses a quantitative approach with surveys and regression analysis to test the influence of entertainment, self-identity, social interaction, and privacy motives on information disclosure. The results showed that entertainment and self-identity motives had a greater influence on information disclosure than other motives. The Close Friends feature provides students with a more private space to share experiences and strengthen their identity, while managing concerns about privacy. These findings strengthen the theories of self-disclosure and Uses and Gratifications, and reveal that social media can provide greater control over privacy without reducing social closeness.